K2ZnSn3Se8: A Non‐Centrosymmetric Zinc Selenidostannate(IV) Featuring Interesting Covalently Bonded [ZnSn3Se8]2− Layer and Exhibiting Intriguing Second Harmonic Generation Activity. Issue 12 (17th May 2017) - Zhou, Molin; Jiang, Xingxing; Yang, Yi; Guo, Yangwu; Lin, Zheshuai; Yao, JJiyong; Wu, Yicheng
Abstract: Non‐centrosymmetric zinc selenidostannate(IV) K2 ZnSn3 Se8 was synthesized. It features interesting covalently bonded [ZnSn3 Se8 ] 2− layers with K + cations filling in the interlayer voids. The phonon spectrum was calculated to clarify its structural stability. Based on the X‐ray diffraction data along with the Raman spectrum, the major bonding features of the title compound were identified. According to the UV/vis‐NIR spectroscopy, K2 ZnSn3 Se8 possesses a typical direct band gap of 2.10 eV, which is in good agreement with the band structure calculations. Moreover, our experimental measurements and detailed theoretical calculations reveal that K2 ZnSn3 Se8 is a new phase‐matchable nonlinear optical material with a powder second harmonic generation (SHG) signal about 0.6 times of that of AgGaS2 . Abstract : In harmony : Zinc selenidostannate(IV) K2 ZnSn3 Se8 has been synthesized that features interesting covalently bonded [ZnSn3 Se8 ] 2− layer and exhibits a moderate second harmonic generation (SHG) response.